ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL BANGUN RUANG SISI DATAR - Bunga Aulia Maulin; Siti Chotimah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study uses descriptive qualitative research. The population taken by the researcher is students from class IX in one of the public schools in Bandung Regency, and the sample in this study were 22 student of class IX-H at the same school. The data collection method use in this study was a test description method with a test containing 8 question which were arranged based on the cognitive bloom level. The results of the test are processed by measuring the percentage of each category indicator in the level of difficulty, namely the very high, hight, quite high, low and very low categories. The results of the study indicate that the difficulties faced by students in answering the flat-sided geometry material are: (a) students have a lot of difficulties in understanding the basic concepts of building space. (b) students still find it difficult to determine which formula should be used and students have difficulty understanding the meaning of the problem. (c) not analyzing the command of the question properly.